PENGARUH LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Dwi Perwitasari Wiryaningtyas (Relawan Jurnal Indonesia, 2022)
This study aims (1) to determine the effect of liquidity (CR), solvency (DER) and profitability (ROA) to partially affect stock prices (2) to determine the effect of liquidity (CR), solvency (DER), and profitability (ROA). ) has a simultaneous effect on stock prices (3) to determine between liquidity (CR), solvency (DER), and profitability (ROA), which have the most dominant influence on stock prices. The method used is quantitative. The result of this research is multiple linear regression equation Y = -1835,668 - 17268,634X1 - 18338,807X2 + 780022,088X3 + e. Partially liquidity (CR) has a negative and significant effect with tcount less than ttable (-2,445) <(-2.028) or sig α 0,019 < 0.05, solvency (DER) has no positive and significant effect, indicating that tcount is smaller than ttable (-0.644) >(2.028) or sig α 0.524 > 0.05, profitability (ROA) has a positive and significant effect, indicating that the value of t is greater than t table (3.743)> (2.028) or sig α 0.001 < 0.05. Simultaneously, liquidity (CR), solvency (DER), and profitability (ROA) have an effect on profit growth with the Fcount value of 6.071, the value is greater than Ftable, namely 2.87 or Fcount 6.071> Ftable 2.87. The variable that has the most dominant influence in this study is profitability (ROA) with a value of 6.071.